Pengaruh edukasi kesehatan melalui media audiovisual terhadap pengetahaun dan sikap ibu tentang Inisiasi Menyusu Dini (IMD) di puskesmas barabaraya dan kassi-kassi kota Makassar Sulawesi Selatan - Handriyani -; Andi Alimuddin; Sundari -; Musliha Mustari; Indah Mauludiyah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: This study aims to analyze the influence of Pocket Book-based media and flipcharts can increase the success of early breastfeeding initiation. Quasi-experimental design research method with Nonequivalent Control Group Design. Sampling in this study were primigravida pregnant women aged 36-40 weeks gestation as many as 56 respondents who were divided into two groups of 28 respondents in the intervention group at the Tamalanrea Jaya Health Center and 28 respondents in the control group at the Anteng Perumnas Health Center. This research was conducted for 48 days on November 26, 2019 until January 13, 2020. Data were analyzed by parametric and non-parametric statistical tests. To see the effect of education on the success of IMD using the fisher exact test.Statistical test results of respondents' characteristics in both the control and intervention groups of inhomogeneous age variation showed that respondents in both groups tended not to be at risk (20-35%) in the control group and interventions in homogeneous occupational and educational characteristics while in the results of statistical tests (p < 0.05) which means that education has a significant effect on the success of IMD